(3JSgjd GdeWdH aj JMUjd GdePgHs - (3YHO GdQMef Hf eMeO Hf CMeO Hf bOGeI GdebOSj GdLeGYjdj GdMfHdj, CHh GdaQL, TeS GdOjf , (B682 (3g`s; (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s ((3YHOGddg Hf YjSi Hf GHQGgje GdebOSi s)
(3ChdgG (B:s
(3Chd GdcJGH s
(3BNQgG (B:s
(3UdGI GdLeGYI s
(3fbd ef fSNI cJHJ SfI (B771s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B206 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B254 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B653s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B12 - (3U (B325 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1809s
Keywords: (3Gdabg GdMfHdjs